2019
DOI: 10.5194/aab-62-465-2019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring insertions and deletions (indels) of <i>MSRB3</i> gene and their association with growth traits in four Chinese indigenous cattle breeds

Abstract: Methionine sulfoxide reductase B3 (MSRB3) is instrumental in ossification and fat deposition, which regulate the growth and development of cattle directly. The purpose of this study was aimed to explore insertions and deletions (indels) in MSRB3 gene and investigate their association with growth traits in four indigenous cattle breeds (Luxi cattle, Qinchuan cattle, Nanyang cattle, and Jiaxian Red cattle). Four indels were identified by sequencing with DNA pool. Association analysis showed that three of them we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Candidate gene is a useful method to investigate the association between phenotypes and genotypes, which is helpful for improving important economical traits in beef cattle [24,25,26]. Recent data have shown that effective molecular markers used in the selection of beef quality traits could bring benefits in the beef industry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene is a useful method to investigate the association between phenotypes and genotypes, which is helpful for improving important economical traits in beef cattle [24,25,26]. Recent data have shown that effective molecular markers used in the selection of beef quality traits could bring benefits in the beef industry [27].…”
Section: Discussionmentioning
confidence: 99%
“…PAFAH1B1 is a highly conserved protein, and studies in mice and other domesticated animals have found that PAFAH1B1 has an important relationship with spermatogenesis and embryonic development ( 40 ). MSRB3 plays an important role in ossification and fat deposition in cattle ( 41 ). KALRN is involved in synaptic regulation ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MSRB3 gene is an important member of the MSL gene family, which regulates the catalyzing effect of methionine-R-sulfoxide to methionine [67]. In four indigenous cattle breeds selected in China, individual SNPs in the MSRB3 gene were associated with traits of body growth and conformation (body weight, rump height, body length, and chest width) [68,69]. The FUT8 gene encodes an enzyme that belongs to the fucosyltransferase family.…”
Section: Discussionmentioning
confidence: 99%